Major depressive episode in mothers during the COVID-19 pandemic: a population-based study in the Southern Brazil - Fernanda Teixeira Coelho; Carolina Coelho Scholl; Jéssica Puchalski Trettim; Jaqueline Buzetto Silveira; Daniele Behling de Mello; Martha Rodrigues dos Santos; Lidiane Aguiar Ferreira; Rafaelle Stark Stigger; Mariana Bonati de Matos; Ricardo Tavares Pinheiro; Luciana de Avila Quevedo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
The COVID-19 pandemic has changed individuals and families, causing adverse psychological effects, especially in young adults, women, and parents. This study aimed to verify the prevalence of current major depressive episode (CMDE) in mothers of preschoolers (up to five years old) and its associated stressors during the COVID-19 pandemic in a municipality in the Southern Brazil. This is a cross-sectional, population-based study with mothers. All mothers were interviewed by telephone call during the COVID-19 pandemic. We used the Mini-International Neuropsychiatric Interview (M.I.N.I. Plus) to assess the presence of CMDE. Statistical analysis was conducted using the chi-square test and a multivariate logistic regression. We evaluated 666 mothers. The prevalence of CMDE was 12.3%. Mothers with financial losses had 2.1 (95%CI: 1.3-3.4) more odds of presenting CMDE than those financially stable. We observed that financial losses were determinant for the higher prevalence of depression in mothers.